If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 7(3x + 9) = 0 Reorder the terms: 1 + 7(9 + 3x) = 0 1 + (9 * 7 + 3x * 7) = 0 1 + (63 + 21x) = 0 Combine like terms: 1 + 63 = 64 64 + 21x = 0 Solving 64 + 21x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-64' to each side of the equation. 64 + -64 + 21x = 0 + -64 Combine like terms: 64 + -64 = 0 0 + 21x = 0 + -64 21x = 0 + -64 Combine like terms: 0 + -64 = -64 21x = -64 Divide each side by '21'. x = -3.047619048 Simplifying x = -3.047619048
| 14+5(x+3)-7x= | | x^2+lnx*3x^2=0 | | 5-(x-9)=-13 | | 40=x+2y | | x=-60-y | | 2x+x+10=0 | | -9x+4x+15-11x= | | 8m^3+12m^2n+6mn^2+n^3=0 | | 0.16(10000)-0.05y=0.05(y+10000) | | 2x^2+x+10=0 | | 6x-3+5=-3x+25 | | 7-x-3= | | -(8x+4y+2)= | | 2n^4-22n^3+56n^2=0 | | x+y=-60 | | 12+-1.6y=3000 | | 400y+250x=3000 | | 6y-12=12 | | 7x+3(x-1)=5x+13 | | (x^4)-(x^3)-3(x^2)+4x-4=0 | | -8w-48=32 | | 6x+9y=333.333 | | 7h+6=76 | | -(2.5x+4.2)=2.7x-x+2(4.28) | | x+21+6=5(x+6) | | 5-2(x-3)=-17 | | 6x+9y=3000 | | 7m+7=56 | | 5n-12=3n-4 | | (4x-1)+7=10x+34 | | 3(y-2)=6(y-1) | | 9(12+1z)=4(3z-3) |